Overview on Recent Advancements in Agriculture (International Journal of Innovative Research in Computer Science & Technology, 2021)
Agriculture is the practice of cultivating  plants & live stocks. Agriculture is the key for the growth  in rising sedentary human living whereas the farming of  the domesticated species creates the food surplus which  enabled the people for living in cities. Agriculture is  significant not only in the supply of food but also in the  provision of raw materials to other industries like sugar,  tobacco, jute, textiles & vegetable oil. Agriculture is the  way of life and also the occupation of the people. Most of  the cultures and customs revolve around agriculture.  Agriculture is the method of farming and the cultivation of  animals, plants, medicinal plants, fungi, and other products  that are utilized for enhancing human life. Agricultural  science is the study of agriculture. This article discusses  current advances in the realm of agriculture as well as their  many ramifications. India will need many types of  agricultural and land-based solutions in the future. India  needs to shift from basic farming towards much efficient,  sustainable & productive farming methods for increasing  the yield and fulfilling the demands of those engaging in  Agriculture.
Keywords: Advancements; Agriculture; Farming; Plant; Sustainable; Yield